Postmodernizm a metoda w naukowym zarządzaniu - Aleksander Lotko (Edukacja Ustawiczna Dorosłych)
The aim of the article is to synthesize considerations on the use of research methods specific to postmodernism in scientific management. Critical analysis of the literature was used as a research method. Scientific management and the paradigm shift of the research methods used are characterized. This change had taken place during the transition from the modernist project to the postmodern reality. The author's contribution is a dialectical juxtaposition of the methodological assumptions of modernism and postmodernism. The article contains a short description of the identified methods as well as conclusions for scientific management that result from the paradigm shift.